THE APPEARANCE OF THE GENUS DESHAYESITES (KAZANSKY, 1914, AMMONOIDEA) IN THE LOWERMOST APTIAN (LOWER CRETACEOUS) OF LA BÉDOULE (SE FRANCE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
New palaeontological and biostratigraphic investigations were carried out at La Bédoule (SE France), which is the stratotype-area of the Bedoulian (Lower Aptian). The levels that directly overlie the last Barremian Pseudocrioceras-bearing bed revealed the occurrence of a fauna characterized by previously undescribed macroconchs of the genus Deshayesites, that we included in Deshayesites bedouliensis n. sp. and in D. aff. consobrinus (d’Orbigny). These forms are associated with the species Deshayesites antiquus Bogdanova, D. oglanlensis Bogdanova, D. cf. weissiformis Bogdanova, D. aff. weissiformis Bogdanova in Delanoy, D. cf. planicostatus Bogdanova, and D. aff. normani Casey. These ammonites characterize the basal Aptian Deshayesites tuarkyricus Zone. This Zone was defined in Turkmenistan but its recognition in the Mediterranean Tethys is confirmed by the present study. Contrary to previous assertions, the genus Prodeshayesites (which pre-dates Deshayesites in northern Germany and southern England), whose FAD was taken to mark the base of the Aptian, is absent at La Bédoule. Prodeshayesites is absent also in Turkmenistan and in all other Mediterranean localities. The FAD of the genus Deshayesites is taken to mark the base of the Aptian in the Mediterranean area.